2017
DOI: 10.1016/j.drugalcdep.2017.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Baclofen and naltrexone effects on alcohol self-administration: Comparison of treatment initiated during abstinence or ongoing alcohol access in baboons

Abstract: Background Baclofen, a GABAB receptor agonist, is under investigation as a pharmacotherapy for alcohol use disorder. Treatment with a pharmacotherapeutic can be initiated during alcohol abstinence or active drinking, which may influence treatment outcomes. This study examined whether baclofen treatment initiated and maintained during alcohol abstinence would reduce alcohol seeking and self-administration upon return to alcohol access, and whether effects differed from treatment initiated and maintained during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Other limitations of the study include relatively short study duration, a lack of positive control e.g., naltrexone, and the inclusion of only male monkeys. In baboons, naltrexone reduced drinking to a degree comparable to our liraglutide effect (Holtyn et al 2017). Finally, both this study and our previous mouse study ( Thomsen et al 2017) tested (sub)chronic GLP-1 receptor agonist administration initiated under conditions of suspended alcohol access (which may reflects aspects relevant to relapse in humans).…”
Section: Discussionmentioning
confidence: 56%
“…Other limitations of the study include relatively short study duration, a lack of positive control e.g., naltrexone, and the inclusion of only male monkeys. In baboons, naltrexone reduced drinking to a degree comparable to our liraglutide effect (Holtyn et al 2017). Finally, both this study and our previous mouse study ( Thomsen et al 2017) tested (sub)chronic GLP-1 receptor agonist administration initiated under conditions of suspended alcohol access (which may reflects aspects relevant to relapse in humans).…”
Section: Discussionmentioning
confidence: 56%
“…Two recent studies ( 49 , 50 ) investigated the effect of baclofen on alcohol self-administration in non-human primates. In both studies, adult male baboons were exposed to a chained schedule of reinforcement with three linked components; sequential completion of RR of each component made alcohol available.…”
Section: Baclofen Effect On Operant Alcohol Self-administrationmentioning
confidence: 99%
“…Treatment with baclofen decreased lever-responding for alcohol, number of alcohol drinks, and amount of self-administered alcohol. Treatment with baclofen was effective when initiated during ongoing alcohol access, but not when initiated during an alcohol-abstinence period preceding alcohol access ( 50 ). These data are in agreement with the results of human studies indicating a greater efficacy of baclofen when treatment was initiated during active drinking [e.g., ( 51 )] rather than after abstinence had been achieved [e.g., ( 52 )].…”
Section: Baclofen Effect On Operant Alcohol Self-administrationmentioning
confidence: 99%
“…We have also demonstrated that seeking and self-administration behaviors associated with alcohol were augmented after abstinence (Weerts et al, 2006), and alcohol-maintained behaviors were more resistant to extinction when compared with behaviors maintained by a preferred, nonalcoholic beverage (Holtyn et al, 2014). In addition, alcohol-seeking and self-administration were reduced by administration of naltrexone, baclofen, and varenicline (Duke, Kaminski, & Weerts, 2014; Holtyn, Kaminski, & Weerts, 2017; Kaminski, Duke, & Weerts, 2012; Kaminski & Weerts, 2014).…”
mentioning
confidence: 99%